Cryptocurrency open innovation payment system: Comparative analysis of existing cryptocurrencies - Valery Titov; Mafura Uandykova; Oleg V. Litviško; Tatyana Kalmykova; Sergey Prosekov; Tomonobu Senjyu (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This study was conducted to evaluate the implementation of an open innovation cryptocurrency financial system using a statistical approach. The data array reflects the actual speed of the cryptocurrency system, expressed in transactions per second (TPS), taken as the average annual speed. The article offers a comprehensive approach for choosing the optimal cryptocurrency financial system. The final analysis shows that the reasons for the adoption of the cryptocurrency financial system are practicality and convenience, as well as efficient transaction time, faster payment, and simplicity of the payment process. The impact of social factors, expected efforts, and conditions of assistance on the attitude to the cryptocurrency financial system were evaluated. In addition, social factors that have a significant impact on the implementation of the cryptocurrency financial system were identified.
Keywords: 650; bitcoin; correlation analysis; cryptocurrency; EOS; velocity